You are what you click : how being selective, positive, and creative can transform your social media experience - Primack, Brian A. (Chronicle Prism, 2021)
"Do you feel guilty about the hours you spend on social media every week? Have you ever felt down after scrolling through an instastar's feed as they appear to be living a far more amazing life than the rest of us? What if a doctor could tell you how to keep both your social media and your sanity? No more deleting all your online social accounts or digital abstinence, in this much needed reprieve amongst a society focused on the negative effects of technology, You Are What You Click not only shows us how what we are consuming online effects our happiness, but gives us a personalized diet for enjoying a healthy relationship with social media based on our personality type. Social media expert, Brian Primack, M.D., Ph.D. argues that we aren't just feeling alone and depressed because of our consumption of social media, phone use, and technology, but because we are using these innovations all wrong. Delivering a realist's guide for anyone with a handle, Primack arms readers with new evidence-based research about how we can transform social media into a tool for inspiration, creativity, and connection. Primack shows us how the nuances of our social media use can impact our health differently depending on which of the five major personality types we identify as: Conscientiousness: efficient, well-organized, dependable, and self-sufficient. Extroversion: talkative, outgoing, and comfortable in the spotlight; Agreeableness: easy going, kind, and affectionate toward others. Openness to Experience: curious and creative, and prefer variety. Neuroticism: reactive and excitable, and often anxious or emotionally unstable. While X amount of hours on social media may create higher levels of depression or anxiety for the "Easy Going" personality type, the same time online could serve as a creative outlet for a "self-sufficient" personality. With short actionable chapters, Primack takes you step by step through unfollowing toxic relationships, filling our feeds with uplifting content, managing our time online, and finding the communities that promote real connection. Just like anyone might eat more vegetables and fruit in their diet to promote physical wellness, Primack shows readers how they can curate their online interactions to promote their mental wellbeing. This surprising and wholly new take on managing our online presence helps readers take back control and discover the benefits of using social media in ways that work for them"--